2017
DOI: 10.1016/j.tox.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A compromised liver alters polychlorinated biphenyl-mediated toxicity

Abstract: Exposure to environmental toxicants namely polychlorinated biphenyls (PCBs) is correlated with multiple health disorders including liver and cardiovascular diseases. The liver is important for both xenobiotic and endobiotic metabolism. However, the responses of an injured liver to subsequent environmental insults has not been investigated. The current study aims to evaluate the role of a compromised liver in PCB-induced toxicity and define the implications on overall body homeostasis. Male C57Bl/6 mice were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…These data suggest that PCB exposures can promote a fibrotic response through a mechanism involving TGF-β production from hepatocytes and MEF2C upregulation. While histologically liver fibrosis was not increased in this model it has been reported in other PCB exposure models that have either longer periods of PCB exposures and/or certain dietary conditions (3,139). These data suggest that fibrosis in response to PCBs should be reevaluated in other model systems and human subjects as the data suggest PCBs promote the early stages of fibrosis (e.g.…”
Section: Aroclor Exposure Activates Hscs Through Hepatocyte-derived Tsupporting
confidence: 50%
See 1 more Smart Citation
“…These data suggest that PCB exposures can promote a fibrotic response through a mechanism involving TGF-β production from hepatocytes and MEF2C upregulation. While histologically liver fibrosis was not increased in this model it has been reported in other PCB exposure models that have either longer periods of PCB exposures and/or certain dietary conditions (3,139). These data suggest that fibrosis in response to PCBs should be reevaluated in other model systems and human subjects as the data suggest PCBs promote the early stages of fibrosis (e.g.…”
Section: Aroclor Exposure Activates Hscs Through Hepatocyte-derived Tsupporting
confidence: 50%
“…Based On the proteomic data I conducted pathway analysis and transcription factor analysis to elucidate mechanism for PCB-mediated steatohepatitis. Previously some PCBs have been shown to activate human and murine aryl hydrocarbon receptor (AhR) and some nuclear receptors [e.g., the pregnane x receptor (PXR) and the constitutive androstane receptor (CAR)]; while inhibiting epidermal growth factor receptor (EGFR) signaling (3,36,96,139,140). Knocking out PXR or CAR modulated but did not prevent the steatohepatitis associated with Aroclor 1260 and high fat diet co-exposures, implicating additional mechanisms (18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PCB-126 can promote liver disease in in vivo [24] and was demonstrated to be the most potent EGFR inhibitor (of the PCB congeners) tested in vitro [1]. PCB-153 worsened steatosis in vivo [25], and was a potent EGFR inhibitor in vitro as well, but less so than PCB-126.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that compromised health or suboptimal lifestyles may exacerbate the toxicity of environmental pollutants. For example, it has been shown that pollutant toxicity is worsened in animal models with NAFLD . This illustrates the idea that individuals in poor health or with underlying disease conditions may be more susceptible to environmental insult or other chemical or nonchemical stressors.…”
Section: What Influences Disease Risk Associated With Environmental Imentioning
confidence: 92%
“…For example, it has been shown that pollutant toxicity is worsened in animal models with NAFLD. 37 This illustrates the idea that individuals in poor health or with underlying disease conditions may be more susceptible to environmental insult or other chemical or nonchemical stressors. Additionally, it is now appreciated that events occurring during pregnancy can play a significant role in the future health and disease risk of the offspring.…”
Section: What Influences Disease Risk Associated With Environmental Imentioning
confidence: 93%